Crystal structure and initial characterization of a novel archaeal‐like Holliday junction‐resolving enzyme from Thermus thermophilus phage Tth15‐6. Issue 2 (24th January 2022) - Ahlqvist, Josefin; Linares-Pastén, Javier A.; Håkansson, Maria; Jasilionis, Andrius; Kwiatkowska-Semrau, Karolina; Friðjónsson, Ólafur H.; Kaczorowska, Anna-Karina; Dabrowski, Slawomir; Ævarsson, Arnþór; Hreggviðsson, Guðmundur Ó.; Al-Karadaghi, Salam; Kaczorowski, Tadeusz; et al.
Abstract : The first structure of a novel archaeal‐like Holliday junction‐resolving enzyme originating from a thermophilic phage was determined and its function in cleaving X‐shaped dsDNA was demonstrated. Furthermore, a novel signature motif for Holliday junction‐resolving enzymes originating from thermophilic bacteriophages is proposed. Abstract : This study describes the production, characterization and structure determination of a novel Holliday junction‐resolving enzyme. The enzyme, termed Hjc_15‐6, is encoded in the genome of phage Tth15‐6, which infects Thermus thermophilus . Hjc_15‐6 was heterologously produced in Escherichia coli and high yields of soluble and biologically active recombinant enzyme were obtained in both complex and defined media. Amino‐acid sequence and structure comparison suggested that the enzyme belongs to a group of enzymes classified as archaeal Holliday junction‐resolving enzymes, which are typically divalent metal ion‐binding dimers that are able to cleave X‐shaped dsDNA–Holliday junctions (Hjs). The crystal structure of Hjc_15‐6 was determined to 2.5 Å resolution using the selenomethionine single‐wavelength anomalous dispersion method. To our knowledge, this is the first crystal structure of an Hj‐resolving enzyme originating from a bacteriophage that can be classified as an archaeal type of Hj‐resolving enzyme. As such, it represents a new fold for Hj‐resolving enzymes from phages. Characterization of the structure of Hjc_15‐6 suggests that it may form a dimer, or even a homodimer of dimers, and activity studies show endonuclease activity towards Hjs. Furthermore, based on sequence analysis it is proposed that Hjc_15‐6 has a three‐part catalytic motif corresponding to E–SD–EVK, and this motif may be common among other Hj‐resolving enzymes originating from thermophilic bacteriophages.